PTH-121 Primary care calprotectin testing for suspected IBD: Does it reduce time to diagnosis or treatment?. Issue 2 (June 2019) - Hicks, Amy; Selinger, Christian
Abstract : Introduction: Primary care faecal calprotectin (FC) was introduced locally in 2014 to help distinguish IBD from IBS with the additional aim of reducing time to IBD diagnosis and treatment. This study examines impact of FC on referral routes, time to diagnosis and treatment. Methods: All patients classified as new referrals to IBD clinics were studied for 2013 and 2016. Of these 762 patients only 248 with a new diagnosis of IBD (248 total) were included. Data on referral routes and dates, faecal calprotectin measurements, and date of first treatment and proxy outcomes for disease severity during the 1st year (steroid use, biologic use, surgery) all at 1 year were collected. Time to diagnosis and treatment was compared using unpaired t-tests. Disease severity was analysed using chi-squared test. Results: There were no significant differences in baseline data between cohorts (mean age 43 years, 50% male, 17% smokers status, 35% CD, 60% UC, 5% IBD-U) and no significant difference in disease severity. The number of patients referred directly to gastroenterology rose from 3% (2013) to 17% (2016), while 10% of diagnoses were made during emergency admissions (unchanged, table 1 ). Referrals via the 2-week wait pathway remained high (38% 2013, 28% in 2016), whilst many had initial investigations at independent centres contracted to provide NHS care (16% in 2013, 24% in 2016). Time from referral to diagnosis of IBD increased non-significantly from 2013 (0.79 months) to 2016 (1.27, p=0.2). 48 patients had FC checked prior to referral and 37.5% of these were referred direct to gastroenterology. Time to diagnosis was marginally longer in patients with FC compared to those without (1.47 vs 0.86 months, p=0.06). Time from diagnosis to treatment reduced from 1.37 (2013) to 0.72 months (2016, p=0.01). Conclusion: FC has contributed to an increased proportion of referrals direct to gastroenterology, but time to diagnosis in patients with FC was marginally longer. There are considerable differences in time to diagnosis and treatment depending on referral routes. Importantly, 30% present via the 2-week wait pathway and 10% as emergency admissions. Further work is required to ensure patients with suspected IBD get referred to the most appropriate service in a timely manner.